Tobacco leaves and roots differ in the expression of proline metabolism-related genes in the course of drought stress and subsequent recovery - Dobrá, Jana; Vanková, Radomira; Havlová, Marie; Burman, Adlai J; Libus, Jiři; Storchová, Helena (Journal of plant physiology, 2011)
In plants, members of gene families differ in function and mode of regulation. Fine-tuning of the expression of individual genes helps plants to cope with a variable environment. Genes encoding proline dehydrogenase (PDH), the key enzyme in proline degradation, and the proline biosynthetic enzyme, Δ(1)-pyrroline-5-carboxylate synthetase (P5CS), play an important role in responses to osmotic and drought stresses. We compared the expression patterns of three PDH and two putative P5CS genes during drought stress progression and subsequent recovery. Whereas the NtPDH1 gene was affected little by dehydration or rehydration, the NtPDH2 gene responded rapidly to both conditions, and was down-regulated under drought. The CIG1 gene, encoding cytokinin-inducible PDH, exhibited an intermediate transcription pattern. Whereas P5CS B was not affected by the stress conditions, the P5CS A gene was highly up-regulated during drought stress. CIG1 and NtPDH1 transcription was not activated, and P5CS A was only partially reduced in leaves within 24-h after rehydration, a re-watering period sufficient for large physiological changes to occur. The lack of activation of tobacco PDH genes and incomplete reduction of the P5CS A gene in leaves within 24-h of rehydration may reflect the need for the protection of plants to potential subsequent stresses. The data indicate that recovery is a specific physiological process following different patterns in leaves and roots.
Keywords: Plant Proteins; Proline; rostlinné proteiny; kyselina abscisová; Time Factors; regulace genové exprese enzymů; 1-pyrrolin-5-karboxylátdehydrogenasa; časové faktory; Proline Oxidase; tabák; listy rostlin; Transcription, Genetic; osmotický tlak; Plant Leaves; Osmotic Pressure; prolinoxidasa; genetická transkripce; rostlinné geny; 1-Pyrroline-5-Carboxylate Dehydrogenase; fyziologický stres; Abscisic Acid; Gene Expression Regulation, Enzymologic; kořeny rostlin; Plant Roots; Stress, Physiological; období sucha; voda; Water; Genes, Plant; Nicotiana; Gene Expression Regulation, Plant; prolin; regulace genové exprese u rostlin; Droughts